Preparation of powdered egg yolk using a mini spray dryer - Ignário,Rene Maria (2007)
Powdered egg is used as an emulsifying agent in emulsion formulations. It is an excellent source of high quality protein, of which the yolk contains 44% and the egg white 56%. Spray drying is a widely applied method for drying aqueous or organic solutions and emulsions in the chemical and food industries. Spray drying can be used to preserve food or simply as a rapid drying method. The objective of this work was to study the viability of obtaining powdered egg yolk powder using a Büchi B-190 Mini Spray Dryer. The egg yolk protein was evaluated by the semi-micro Kjeldahl method. It was concluded that the use of the Büchi B-190 Mini Spray Dryer to produce powdered egg yolk is perfectly feasible.